Pre-Treatment Of Natural Graphite As Starting Material For Carbon Nanotube Synthesis - Abidin, Z.R.Z.; Ismail , A.F.; Aziz, M.; Sanip, S.M.; Buang, N. (2003)
In the push for renewable energy and cleaner fuels, hydrogen is an ideal candidate for this purpose. This is due to the high-energy value and lack of environment pollution generated on combustion, compared with conventional fossil fuel sources. Several researches have been done on Carbon Nanotube (CNT) as potential hydrogen storage material. This research was conducted to determine the suitable base material to synthesis CNT. The effects of heat treatment were looked into for natural graphite. The materials were heated at 400 "C and 800 "C for 4 to 24 hours. The surface area and composition of natural graphite were studied before and after treatment. The surface area analyses were carried out using Nitrogen Gas Adsorption technique, while the percentage carbon composition were determined using Energy Dispersive X-ray Analysis (EDAX). Heat treatment resulted in the change of surface areas with the increment of temperature and time. The percentage of carbon content in natural graphite after heat treatment at 800 'C still remain in the range of 90%, indicating the stability of graphite. Conclusively, natural graphite is suitable to be use as starting material for CNT.